Chrysoperla carnea (Stephens) : a New Record of Insect Predator on Teak Pests, Hyblaea puera Cramer and Eutectona machaeralis (Walker) - Roychoudhury, N.; Chandra, Subhash (Indian Forester, 2012)
No abstract